The linguistic-cultural dictionary as a means of forming sociocultural competence - Ященко, А.; Клочко, Т. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2019)
. The article deals with national-oriented linguistic-cultural dictionaries as a means of formation of sociocultural competence. It is found out that linguistic-cultural dictionaries explain the peculiarities of application, additional semantic load, connotations of words and word combinations, as well as provide important background cultural information. The linguistic-cultural dictionary is a means of reflecting and comprehending the culture of the society, its national uniqueness. Modern linguistic-cultural dictionaries are created on the basis of previously published book versions of such dictionaries and are supplemented with multimedia content, i.e. verbal texts, reproductions, photographs, audio recordings, video fragments, panoramas, karaoke, video lectures, as well as interactive tasks. Linguistic-culturaldictionaries help to form sociocultural competence, which, in turn, gives foreign students the opportunity to feel free in various sociocultural situations, to be versatile, to have a wide outlook, to understand the laws of culture development as a process of creation, preservation and transmission of universal values, to orientate themselves in traditions, realities, customs, spiritual values not only of their own people, but also of other nations, to be able to speak out and communicate effectively. The linguistic-culturaldictionary is one of the important types of educational lexicographical works, its purpose is to present various thematic groups of nationally significant lexical units of the language, to acquaint foreigners with the most important national realities, to help students to use equivalent and background lexicon correctly.